The protean Virgil material form and the reception of the classics - Kallendorf, Craig 1954-2023 (Classical presences, 2015)
Taking Virgil's poetry as a case study, 'The Protean Virgil' argues that when we try to understand different readers' varying responses to the same text over time, we should take into account the physical form in which they read the text (e.g. manuscripts, books, or computerized files) as well as the text itself.